The role of African Christian churches in dealing with sexual violence against women : the case of the Democratic Republic of Congo, Rwanda and Liberia - Le Roux, Elisabet (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.